Iron-catalyzed photoreduction of carbon dioxide to synthesis gas. Issue 10 (11th January 2016) - Alsabeh, Pamela G.; Rosas-Hernández, Alonso; Barsch, Enrico; Junge, Henrik; Ludwig, Ralf; Beller, Matthias
Abstract : Photocatalytic processes to convert CO2 to useful products including CO and HCOOH are of particular interest as a means to harvest the power of the sun for sustainable energy applications. Herein, we report the photocatalytic reduction of CO2 using iron-based catalysts and visible light generating varying ratios of synthesis gas. Abstract : Photocatalytic processes to convert CO2 to useful products including CO and HCOOH are of particular interest as a means to harvest the power of the sun for sustainable energy applications. Herein, we report the photocatalytic reduction of CO2 using iron catalysts and visible light generating varying ratios of synthesis gas. In most cases, either a 1 : 1 CO : H2 ratio was observed or the selectivity was skewed slightly towards CO with combined TONs reaching nearly 100. Operando FTIR studies revealed the favourable activity of FeBr2 as an iron precursor to generate the catalytically active species Fe(CO)3 bpy. The Fe(CO)3 bpy complex was then synthesized and successfully applied as a catalyst at various loadings providing almost 300 total TONs for syngas formation. This represents the highest activity reported thus far for an iron-based system in photocatalytic CO2 reduction.